Caterpillar attack triggers accumulation of the toxic maize protein RIP2. Issue 3 (7th November 2013) - Chuang, Wen‐Po; Herde, Marco; Ray, Swayamjit; Castano‐Duque, Lina; Howe, Gregg A.; Luthe, Dawn S.
Summary: Some plant‐derived anti‐herbivore defensive proteins are induced by insect feeding, resist digestion in the caterpillar gut and are eliminated in the frass. We have identified several maize proteins in fall armyworm ( Spodoptera frugiperda ) frass that potentially play a role in herbivore defense. Furthermore, the toxicity of one of these proteins, ribosome‐inactivating protein 2 (RIP2), was assessed and factors regulating its accumulation were determined. To understand factors regulating RIP2 protein accumulation, maize ( Zea mays ) plants were infested with fall armyworm larvae or treated with exogenous hormones. The toxicity of recombinant RIP2 protein against fall armyworm was tested. The results show that RIP2 protein is synthesized as an inactive proenzyme that can be processed in the caterpillar gut. Also, caterpillar feeding, but not mechanical wounding, induced foliar RIP2 protein accumulation. Quantitative real‐time PCR indicated that RIP2 transcripts were rapidly induced (1 h) and immunoblot analysis indicated that RIP2 protein accumulated soon after attack and was present in the leaf for up to 4 d after caterpillar removal. Several phytohormones, including methyl jasmonate, ethylene, and abscisic acid, regulated RIP2 protein expression. Furthermore, bioassays of purified recombinant RIP2 protein against fall armyworm significantly retarded caterpillar growth. We conclude that the toxic protein RIP2 is induced by caterpillar feeding and is one of a potential suite of proteins that defend maize against chewing herbivores.